Identification of potential therapeutic targets in urothelial bladder carcinoma of Chinese population by targeted next-generation sequencing. Issue 8 (2nd August 2020) - Wang, Tao; Liu, Zhengsheng; Wang, Xuegang; Bai, Peide; Sun, Anran; Shao, Zhiqiang; Luo, Rongtuan; Wu, Zhun; Zhang, Kaiyan; Li, Wei; Xiao, Wen; Duan, Bo; et al.
ABSTRACT: Patients with urothelial carcinoma (UC) of the bladder have a high risk of death in China. However, a lack of comprehensive molecular profiling in Chinese Han population hinders the development of targeted therapies for bladder cancer. In our present study, we collected fresh bladder tumors from low-grade (T1, N0, M0, G1) non-muscle invasive bladder cancer (NMIBC) patients (n = 16) and high-grade (T2-4, N0, M0, Gx) muscle-invasive bladder cancer (MIBC) patients (n = 16) with their paired normal bladder tissues, and subjected the total genomic DNAs to targeted next-generation sequencing (NGS) for 94 cancer-associated genes. NGS results showed that 30.9% of detected genes (29/94) was mutated in 32 urothelial carcinoma bladder tissues. Furthermore, our results and ICGC database showed that FGFR3, KMT2D, TP53, KDM6A, and ARID1A were the most frequently mutated genes in UC patients. Of note, NMIBC and MIBC displayed distinguishable genomic alterations. FGFR3, KMT2D, AKT1, ARID1A, and STAG2 were the most frequently mutated genes in NMIBC patients, whereas mutations of TP53, CREBBP, FGFR3, KDM6A, KMT2D, and ARID1A were frequently detected in MIBC. Intriguingly, gene ontology and clustering analysis revealed that these frequently mutated genes were highly enriched in signaling pathways responsible for cancer development. Taken together, the mutation frequency of genes associated with UC development in NMIBC and MIBC was screened out in Chinese Han population and elucidation of the related mechanisms provides theoretical basis and technical support for the development of early diagnosis and therapeutic strategies in UC.